2015
DOI: 10.1186/s13006-015-0047-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated exclusive breastfeeding practices of urban women in Addis Ababa public health centers, Ethiopia: a cross sectional study

Abstract: BackgroundExclusive breastfeeding (EBF) is the best nutrition for the children during the first 6 months of life, yet despite knowing the clear benefits, the practice of EBF is low. The aim of the study is to determine prevalence of exclusive breastfeeding practice and associated factors in Addis Ababa.MethodsA facility based cross-sectional study with internal comparison was conducted among 648 mothers attending immunization sessions in all public health centers in Addis Ababa, Ethiopia, in February 2011. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
76
9
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 13 publications
27
76
9
4
Order By: Relevance
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 73%
“…A study in Addis Ababa, Ethiopia found the prevalence of EBF under six months was 29.3 % [9]. A study in Arbaminch, Ethiopia showed that 55.6 % exclusively breastfed their children for six months.…”
Section: Ethiopian Contextmentioning
confidence: 99%
“…The prevalence of exclusive breast feeding in this study higher than that of reported in previous study in Brazil, 4%, Bangladesh, 16%, Saudi Arabia, 8.3 %, Rwanda, 38%, Congo, 2.8%, Malaysia, 43.1%, Nigeria ,16.4%, Meerut, 34.8% [13][14][15][16][17]33,35]. In Ethiopia reported low prevalence in Mizan Aman town, 26.4 %, Addis Ababa ,29.3 %, North Gondar, 35.9%, Southern Ethiopia, 48.2%, Arba Minch Zuria, 55.6% , Gedeo , 57.6 %, Debre Markos, 60.8%, District of Debre Markos town and Gozamen, 55% and 64% respectively [19][20][21][22][23][24][25][26]. Higher prevalence reported in Debre Berhan, 68.6 %, Goba district, south east, 71.3%, and Dubti town, afar region, and 81.1 % respectively [27,30,34].…”
Section: Discussionmentioning
confidence: 99%
“…Study showed that the prevalence of EBF in Brazil 4% , Bangladesh 16%, Rwanda 38%, Saudi Arabia 8.3 %, Congo 2.8 %, of infants were exclusively breastfed [14][15][16][17]. In Ethiopia the range of prevalence of EBF less than six months were 24.4 % -81.1% [19][20][21][22][23][24][25][26][27][28][29]. Currently, the Health Sector Transformation Plan Two (HSPII) has set a target to increase exclusive breastfeeding from 52% to 72% in Ethiopia by the end of 2020 [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation